2014
DOI: 10.1007/s11250-014-0738-7
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of contagious bovine pleuropneumonia (CBPP) in Mali

Abstract: A serological survey to determine the prevalence of contagious bovine pleuropneumonia (CBPP) in Mali was carried out by using the competitive enzyme linked-immunosorbent test (c-ELISA) on 8007 serum samples systematically collected from 199 cattle herds collected throughout the whole country. Results showed a national prevalence of 18.11 % at the individual level and 85.93 % at the herd level. Significant variations in the individual prevalence were observed between regions of the country and ranged from 4.63 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
2
9
1
Order By: Relevance
“…In addition, Andrews and Windsor (2004) reported that CBPP is prevalent in older animals. This might be due to the chance by age for longer time of exposure to pathogens, low level of immunity at older age, and the persistence of sequestrum in older animals as compared to younger ones who may benefit from the maternal immunity to some extent (Séry et al, 2015;Dar et al, 2018). In contrast to our findings, Gizaw (2004) reported no significance difference (P>0.05) regarding the prevalence of CBPP among cattle, in relation to their age.…”
Section: Resultscontrasting
confidence: 99%
“…In addition, Andrews and Windsor (2004) reported that CBPP is prevalent in older animals. This might be due to the chance by age for longer time of exposure to pathogens, low level of immunity at older age, and the persistence of sequestrum in older animals as compared to younger ones who may benefit from the maternal immunity to some extent (Séry et al, 2015;Dar et al, 2018). In contrast to our findings, Gizaw (2004) reported no significance difference (P>0.05) regarding the prevalence of CBPP among cattle, in relation to their age.…”
Section: Resultscontrasting
confidence: 99%
“…Our results were lower to those of Séry et al in Mali where 8007 sera samples were routinely collected from 199 herds of cattle throughout the country. The results showed a national prevalence of 18.11% at the individual level and 85.93% at the herd level ( 15 ). This difference can be explained by the sampling method.…”
Section: Discussionmentioning
confidence: 99%
“…According to Abdella and Yune [ 8 ], outbreaks were reported in 20 African countries like Ghana, Burkina Faso, Senegal, Congo, and so on. In Mali the national prevalence of 18.11% at the individual level and 85.93% at the herd level has been reported [ 15 ]. The highest number of cases was recorded in Ethiopia in the last few years [ 8 ].…”
Section: Introductionmentioning
confidence: 99%